0=ln(8x+2)

Simple and best practice solution for 0=ln(8x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0=ln(8x+2) equation:


Simplifying
0 = ln(8x + 2)

Reorder the terms:
0 = ln(2 + 8x)
0 = (2 * ln + 8x * ln)
0 = (2ln + 8lnx)

Solving
0 = 2ln + 8lnx

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-2ln' to each side of the equation.
0 + -2ln = 2ln + -2ln + 8lnx
Remove the zero:
-2ln = 2ln + -2ln + 8lnx

Combine like terms: 2ln + -2ln = 0
-2ln = 0 + 8lnx
-2ln = 8lnx

Add '-8lnx' to each side of the equation.
-2ln + -8lnx = 8lnx + -8lnx

Combine like terms: 8lnx + -8lnx = 0
-2ln + -8lnx = 0

Factor out the Greatest Common Factor (GCF), '-2ln'.
-2ln(1 + 4x) = 0

Ignore the factor -2.

Subproblem 1

Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(1 + 4x)' equal to zero and attempt to solve: Simplifying 1 + 4x = 0 Solving 1 + 4x = 0 Move all terms containing l to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 4x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 4x = 0 + -1 4x = 0 + -1 Combine like terms: 0 + -1 = -1 4x = -1 Add '-4x' to each side of the equation. 4x + -4x = -1 + -4x Combine like terms: 4x + -4x = 0 0 = -1 + -4x Simplifying 0 = -1 + -4x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 2(3w+8)=40 | | a+bxt=c | | h-5=6 | | 12a+5a-3a^2= | | 10(h+10)=110 | | 6ln(5x+4)=22 | | 5n+6-3n=-18 | | 7-3x=x-8+4x | | 4x+20/4= | | 4x^3+7x^2-20x-35=0 | | 5n-3n=-18 | | 6x+1=2x+5 | | 0=-x^2-19x-18 | | 50-18=4(x-3) | | 7-21g/7= | | 14x-262=5x-10 | | -(3-3a)=3(a-11) | | x=w^2-v^2 | | 5x^3-30x^2+25x= | | x^3-9x^2+22x-10=0 | | 14-8x=170-36x | | 0=6x^2+24x+2 | | 15c(2c-5)= | | -2(7+5b)+3(2b-3)= | | 2x+x-11+-7x=15 | | -136-8x=170-36x | | G(x)=-x^2-19x-18 | | -12m+8=-13m | | 19=7m+5(3-m) | | 2x-45=6 | | w^2=x+v^2 | | 7(6x+2)= |

Equations solver categories